William Castle Dodge papers - Dodge, William Castle, 1827-1914.
Holograph draft of "The National Capital, its Location and Government" (ca. 1909), and British patent for a firearm design.
Inventor and author.
Collection material in English.
Keywords: Firearms; Washington (D.C.) -- History; Authors; Inventors